2021
DOI: 10.1111/cns.13692
|View full text |Cite
|
Sign up to set email alerts
|

CHD4 variants are associated with childhood idiopathic epilepsy with sinus arrhythmia

Abstract: Aims: CHD4 gene, encoding chromodomain helicase DNA-binding protein 4, is a vital gene for fetal development. In this study, we aimed to explore the association between CHD4 variants and idiopathic epilepsy. Methods: Trios-based whole-exome sequencing was performed in a cohort of 482 patients with childhood idiopathic epilepsy. The Clinical Validity Framework of ClinGen and an evaluating method from five clinical-genetic aspects were used to determine the association between CHD4 variants and epilepsy. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
(105 reference statements)
0
9
0
Order By: Relevance
“…None of them was discovered in the homozygotes of all population according to gnomAD (table 1). When the burden of recessive variants was analysed, the BSN variants in the present cohort were significantly more than the expected number by chance in the East Asian population (minor allele frequency from gnomAD (MAF) <0.005, p=2.316×10 5 ).…”
Section: Evaluating the Bsn Gene As A Novel Candidate Epilepsy Genementioning
confidence: 64%
See 1 more Smart Citation
“…None of them was discovered in the homozygotes of all population according to gnomAD (table 1). When the burden of recessive variants was analysed, the BSN variants in the present cohort were significantly more than the expected number by chance in the East Asian population (minor allele frequency from gnomAD (MAF) <0.005, p=2.316×10 5 ).…”
Section: Evaluating the Bsn Gene As A Novel Candidate Epilepsy Genementioning
confidence: 64%
“…WES was performed with NextSeq2000 sequencing instruments (Illumina, San Diego, California, USA). Sequence alignment and variant calling were performed according to standard procedures as previously described 4 5 20. The potentially disease-causing variants were analysed with an individualised protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The proband's phenotype similarity score, calculated against the SIHIWES clinical synopsis at OMIM #617159, was low and without statistical significance [PhenSSc 1.29 (p = 0.1960; MaxSSc 3.02; MaxDiseaseSSc 3.64)]. Therefore, the clinical features reported in 44 patients with SIHIWES or CHD4-NDD were extensively revised and subdivided according to the pathogenic CHD4 variant (Tables S4 and S5) [19][20][21][22][23][24]. Indeed, the PhenSSC calculated against the revised clinical features reference list was 2.33, and near to statistical significance (p = 0.0587; MaxSSc 3.02; MaxDiseaseSSc 4.2) (Tables 1 and S6).…”
Section: Characterization Of the Genomic And Genetic Variants And Aff...mentioning
confidence: 99%
“…Therefore, this LoF CHD4 variant is the most likely cause of the patient's phenotype, establishing the diagnosis of SIHIWES or CHD4-NDD. The ratio between variants-patients with a specific clinical feature per total number of patients-variants (n = 44) with available data is reported [19][20][21][22][23][24]. Additional information is available in Tables S4-S6.…”
Section: Characterization Of the Genomic And Genetic Variants And Aff...mentioning
confidence: 99%
“…Monogenic abnormalities only account for 2–8% of IGEs ( Weber and Lerche, 2008 ; Prasad et al, 2013 ). Exome-based genetic screening studies have demonstrated that over twenty genes were associated with IGEs, such as CACNA1H , CACNB4 , CASR , CHD4 , CLCN2 , EFHC1 , GABRD , GABRA1 , GABRG2 , GABRB3 , HCN2 , KCC2 , KCNMA1 , RORB , SCN1A , SLC12A5 , SLC2A1 , RYR 2, and THBS1 ( DiFrancesco et al, 2011 ; Striano et al, 2012 ; Kahle et al, 2014 ; Rudolf et al, 2016 ; Santolini et al, 2017 ; Wang et al, 2017 ; Abou El Ella et al, 2018 ; Li et al, 2018 ; Yap and Smyth, 2019 ; Chan et al, 2020 ; Liu et al, 2021 ). Recent studies also identified several copy number variants associated with IGEs, such as duplication at 8q21.13-q22.2 and microdeletions at 1q21.1, 15q11.2, 15q13.3, and 16p13.11 ( de Kovel et al, 2010 ; Kirov et al, 2013 ; Møller et al, 2013 ; Jähn et al, 2014 ; Rezazadeh et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%